2021
DOI: 10.3390/cells10020420
|View full text |Cite
|
Sign up to set email alerts
|

Potential Treatment of Lysosomal Storage Disease through Modulation of the Mitochondrial—Lysosomal Axis

Abstract: Lysosomal storage disease (LSD) is an inherited metabolic disorder caused by enzyme deficiency in lysosomes. Some treatments for LSD can slow progression, but there are no effective treatments to restore the pathological phenotype to normal levels. Lysosomes and mitochondria interact with each other, and this crosstalk plays a role in the maintenance of cellular homeostasis. Deficiency of lysosome enzymes in LSD impairs the turnover of mitochondrial defects, leading to deterioration of the mitochondrial respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…KS and QS). Nevertheless, this build-up does not fully explain the pathophysiology of the disease, and it has been reported that the abnormal lysosomal function may alter other lysosomal enzymes, such as β-hexosaminidases (Hex) 36 , 37 , as well as lead to an increase in cellular oxidative stress 3 , 4 , 38 . In this sense, we observed a lower total Hex activity in all the untreated MPS IVA fibroblasts (fold change: 0.44–0.84) compared to WT levels (4089 ± 648 U/mg) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…KS and QS). Nevertheless, this build-up does not fully explain the pathophysiology of the disease, and it has been reported that the abnormal lysosomal function may alter other lysosomal enzymes, such as β-hexosaminidases (Hex) 36 , 37 , as well as lead to an increase in cellular oxidative stress 3 , 4 , 38 . In this sense, we observed a lower total Hex activity in all the untreated MPS IVA fibroblasts (fold change: 0.44–0.84) compared to WT levels (4089 ± 648 U/mg) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the TRAP1 agonists to increase the residual activity of mutant LSD enzymes ( Figure 4 E) suggests that they may be of therapeutic value in diseases in which the protein defect is an ER-targeted protein, such as cystic fibrosis or one of the more than 60 LSDs ( Carlile et al., 2007 ; Gelsthorpe et al., 2008 ). Thus, therapeutics that can target and activate TRAP1 may be of great benefit for many devastating disorders ( Davis et al., 2021 ; Klein and Mazzulli, 2018 ; Kuk et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a debate as to whether the lysosomal pH is increased or overly acidified in mucolipidosis type IV cells [62][63][64]. An increased lysosomal pH can be present in some other lysosomal storage diseases [65,66], e.g., in skin fibroblasts from patients with mucolipidosis type II [67], which results from a deficiency in N-acetylglucosamine-(GlcNAc) 1-phosphotransferase activity. Alongside potentially favoring iron retention within the lysosome, thereby contributing to a functional iron deficiency, an elevated lysosomal pH can impair the activity of various lysosomal enzymes and possibly perturb calcium homeostasis, e.g., through TRPML1 disruption [66,68].…”
Section: Mucolipidosis Type IV Causes the Dysfunction Of Trpml1 A Lys...mentioning
confidence: 99%